Effect of calcium chloride on anthracnose disease and postharvest quality of red-flesh dragon fruit (Hylocereus polyrhizus) - Awang, Yahya; Abdul Ghani, Muhd Azlan; Sijam, Kamaruzaman; Mohamad, Rosli (Academic Journals, 2011)
The study was conducted to examine the effects of CaCl 2 postharvest treatment on development of anthracnose, measured as lesion size and quality of red-flesh dragon fruit (Hylocereus polyrhizus). Fully matured fruits were treated with varying concentrations of Ca by soaking the fruits for 30 min in solutions containing 0, 1.0, 2.0, 3.0 and 4.0 CaCl 2 gL -1 . After drying, the fruits were inoculated with spore suspensions of Colletotrichum gloeosporioides (10 6 spores L -1). Calcium chloride applied at varying concentrations did not produce significant effect on anthracnose incidence, but the size of lesion was linearly reduced with increasing Ca concentration. Calcium chloride application as postharvest treatment markedly elevated fruit Ca content especially in the fruit peel, but without influencing the N, P, K and Mg contents. Fruit firmness increased with Ca application while pH, soluble solids concentration and titratable acidity were not affected by the treatment. The effect of anthracnose on firmness, pH, SSC and TA of the fruits were reduced with CaCl 2 treatments.